Impact of english conversational clubs on students' speech anxiety in english clases - Garcés Mesa, Jasbleidy; Hernandez Vargas, Astrid Carolina (Universidad Católica Luis Amigó, 2023)
This case study research aims to analyze how the implementation of English conversational clubs impacts the speech anxiety of English students, which is a barrier that prevents students from developing correct speaking skills in the process of English learning. The group of participants selected was made of 3 English students from a language center located in the municipality of Bello, Antioquia. The data collection techniques involved a conversation club inside a focus group, a semi-structured interview, and a journal. The results showed the important characteristics of the conversational clubs as a way to combat the students’ speech anxiety, how the English conversational club raised their awareness regarding the learning English process, besides, the multiple feelings and obstacles that interfered with when the students spoke in English. Therefore, we invite teachers to look deeper into conversational clubs and take them into consideration for future class planning or institutional curriculum as a strategy to improve oral production in English.
Keywords: Speech anxiety; Oral production of English; Conversational clubs; English oral activities; a